Optical-microwave sensor for real-time measurement of water contamination in oil derivatives - Abdulsattar, Rusul Khalid; Alibakhshikenari, Mohammad; Virdee, Bal S.; Sharma, Richa; Elwi, Taha A.; Kouhalvandi, Lida; Hassain, Zaid A. Abdul; Ali, Syed Mansoor; Tokan, Nurhan Turker; Livreri, Patrizia; Falcone, Francisco; Limiti, Ernesto (ELSEVIER GMBH, 2023)
This paper presents a novel microwave sensor using optical activation for measuring in real-time the water contamination in crude oil or its derivatives. The sensor is constructed from an end-coupled microstrip resonator that is interconnected to two pairs of identical fractal structures based on Moore curves. Electromagnetic (EM) interaction between the fractal curves is mitigated using a T-shaped microstrip-stub to enhance the performance of the sensor. The gap in one pair of fractal curves is loaded with light dependent resistors (LDR) and the other pair with microwave chip capacitors. The chip capacitors were used to increase the EM coupling between the fractal gaps to realize a high Q-factor resonator that determines the sensitivity of the sensor. Empirical results presented here show that the insertion-loss of the sensor is affected by the change in LDR impedance when illuminated by light. This property is used to determine the amount of water contaminated oil. The sensitivity of the sensor was optimized using commercial 3D EM solver. The measurements were made by placing a 30 mm diameter petri dish holding the sample on top of the sensor. The petri dish was filled up to a height of 10 mm with the sample of water contaminated crude oil, and the measurements were done in the range between 0.76 GHz and 1.2 GHz. The Q-factor of the oil sample with no water contamination was 70 and the Q-factor declined to 20 for 100% contamination. The error in the measurements was less than 0.024%. The sensor has dimensions of 0.127 & lambda;o x 0.127 & lambda;o x 0.004 & lambda;o and represents a new modality. Compared to existing techniques, the proposed sensor is simple to use, readily portable and is more sensitive.
Keywords: Microstrip sensor; Electromagnetic (EM) spectrum; Fractal curves; light dependent resistors (LDR); Engineering; Telecommunications